Decision-making framework for using ambient assisted living. Issue 2 (31st July 2020) - Alsulami, Majid H.; Alsaqer, Mohammed S.; Atkins, Anthony S.
Abstract : Purpose: Technology plays an important role in assisting elderly people to live independently, longer and improve their quality of life and health, in supporting their daily activities, etc. The ageing population becomes a global phenomenon. The population of Saudi Arabia continues to age (>60 years of age) currently (5%) compared to other group ages. In 2050, it will increase rapidly to 20.9% of the Saudi population. The current research aims at examining the barriers that health-care providers in the Kingdom of Saudi Arabia are experiencing in the adoption of ambient assisted living (AAL) technologies among the elderly. The study aims to identify a challenging issue with the increasing the number of elderly among the population in the country, which has highlighted the need to use AAL technology to improve the quality of life among the elderly. Design/methodology/approach: This study involved a community of practice (CoP) study as a method of data collection where data collected were presented and discussed in line with the existing literature review findings. Findings: In total, 14 factors were identified in this study and discussed in the context of Saudi Arabia, which resulted in developing a decision-making framework for using AAL by health-care providers. Those factors are essential in boosting the usage of technology in improving elderly health in Saudi Arabia. Research limitations/implications: This study includes implications for developing a decision-making framework for using AAL. Social implications: This study clarifies that technology can connect elderly people with society. Originality/value: In total, 14 factors were identified in this study and discussed in the context of Saudi Arabia.